2017
DOI: 10.4172/2472-0437.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Effects of Sodium Citrate, Calcium Nitrite and Hexamine as Corrosion Inhibitor in Concrete

Abstract: In the present study the effect of sodium citrate, calcium nitrate, and hexamine on corrosion of steel was analyzed. The effect of inhibitor on normal consistency of cement, initial and final setting time of cement, compressive strength of cement, soundness of cement and compressive strength of concrete were also analyzed. The results of the study also concluded that hexamine and calcium nitrite are more efficient inhibitor. It showed 45% and 25% inhibitor efficiency at the denseness of 0.5% hexamine and 0.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It may be concluded that sodium citrate was the component of most single significance but that its use may also have led to a series of additional complex reactions resulting in far greater retardation than when used alone. As observed earlier, the retarding effect of sodium citrate was likely due to the adsorption of citrate ions on the cement particles by complexation with calcium ions, which prevents access to water [34,35,36].…”
Section: Resultsmentioning
confidence: 98%
“…It may be concluded that sodium citrate was the component of most single significance but that its use may also have led to a series of additional complex reactions resulting in far greater retardation than when used alone. As observed earlier, the retarding effect of sodium citrate was likely due to the adsorption of citrate ions on the cement particles by complexation with calcium ions, which prevents access to water [34,35,36].…”
Section: Resultsmentioning
confidence: 98%
“…Corrosion inhibitors are charactedized in following types: Cathodic, Anodic and Mixed, depending on whether they hinder the corrosion reaction at the anodic or cathodic sites or whether both are involved [5,35].…”
Section: Types Of Inhibitorsmentioning
confidence: 99%
“…Quraishi et al [43] studied the effect of sodium citrate, calcium nitrate, and hexamine on corrosion of steel. In this study, they reported the effect of inhibitor on normal consistency of cement, initial and final setting time of cement, compressive strength of cement, soundness of cement and compressive strength of concrete .The results of the study also concluded that hexamine and calcium nitrite are more efficient inhibitor.…”
Section: Mixed Inhibitorsmentioning
confidence: 99%
“…In the presence of CNI, concrete setting times could be delayed (M.A. Quraishi, et. al., 2016;Hansson C.M.…”
Section: Introductionmentioning
confidence: 99%
“…Because CNI could modify the setting time and hydration rate of a cementitious matrix (M.A. Quraishi, et al, 2016;Hansson C.M. et al, 1998), it is expected that the internal curing method with SAP could decrease these mentioned effects.…”
mentioning
confidence: 99%